ВПЛИВ ФАХОВОЇ ПРАКТИКИ НА ФОРМУВАННЯ У СТУДЕНТІВ ПРОФЕСІЙНО ЗНАЧУЩИХ УМІНЬ (Pedagogy of Higher and Secondary Education, 2012)
У статті проаналізовано вплив фахової практики на формування у студентів професійно значущих вмінь. Визначено та описано вміння майбутніх учителів природничих дисциплін. Описано та обґрунтовано  рівень впливу фахової практики на професійно значущі вміння майбутніх учителів природничих дисциплін.Ключові слова: професійно значущі вміння, фахова практика, майбутній учитель.  In the article influence of professional practice is analysed on forming for students professionally meaningful abilities. Certainly and ability of future teachers of natural disciplines is described. The level of influence of professional practice is described and grounded  on professionally meaningful abilities of future teachers of natural disciplines. Key words: professionally meaningful abilities, professional practice, future teacher.
Keywords: professionally meaningful abilities; professional practice; future teacher